Intrauterine Growth Restriction Promotes Postnatal Airway Hyperresponsiveness Independent of Allergic Disease - Kalotas, Jack O.; Wang, Carolyn J.; Noble, Peter B.; Wang, Kimberley C. W. (Frontiers in Medicine, 2021)
Introduction: Intrauterine growth restriction (IUGR) is associated with asthma. Murine models of IUGR have altered airway responsiveness in the absence of any inflammatory exposure. Given that a primary feature of asthma is airway inflammation, IUGR-affected individuals may develop more substantial respiratory impairment if subsequently exposed to an allergen. This study used a maternal hypoxia-induced mouse model of IUGR to determine the combined effects of IUGR and allergy on airway responsiveness. Methods: Pregnant BALB/c mice were housed under hypoxic conditions (10.5 % O2) from gestational day (GD) 11-GD 17.5 (IUGR group; term=GD 21). Following hypoxic exposure, mice were returned to a normoxic environment (21 % O2). A second group of pregnant mice were housed under normoxic conditions throughout pregnancy (Control). All offspring were sensitised to ovalbumin (OVA) and assigned to one of four treatment groups: Control – normoxic and saline challenge; IUGR – hypoxic and saline challenge; Allergy – normoxic and OVA challenge; and IUGR + Allergy – hypoxic and OVA challenge. At eight weeks of age, and 24 hours post-aerosol challenge, mice were tracheostomised for methacholine challenge and assessment of lung mechanics by the forced oscillation technique, and lungs subsequently fixed for morphometry. Results: IUGR offspring were lighter than Control at birth and in adulthood. Both Allergy and IUGR independently increased airway resistance after methacholine challenge. The IUGR group also exhibited an exaggerated increase in tissue damping and elastance after methacholine challenge compared with Control. However, there was no incremental effect on airway responsiveness in the combined IUGR + Allergy group. There was no impact of IUGR or Allergy on airway structure and no effect of sex on any outcome. Conclusion: IUGR and aeroallergen independently increased bronchoconstrictor response, but when combined the pathophysiology was not worsened. Findings suggest that an association between IUGR and asthma is mediated by baseline airway responsiveness rather than susceptibility to allergen.